Isolation of human glucose-6-phosphate dehydrogenase (G6PD) cDNA clones: primary structure of the protein and unusual 5' non-coding region. - Persico, M G (1986)
Glucose-6-phosphate dehydrogenase (G6PD) is an ubiquitous enzyme which by determining the NADPH level has a crucial role in NADPH-mediated reductive processes in all cells (1). The structural gene for G6PD, Gd, is X-linked in mammals and on the basis of its expression in many tissues, it can be regarded as a typical "housekeeping" gene (2). Over 300 variants of the protein are known, many of which have deficient enzyme activity. Nearly 100 of these variants are polymorphic in various populations (3). The mammalian enzyme is a homodimer or a homotetramer with a subunit molecular weight of approximately 56000 daltons (4). Here we report the isolation of cDNA clones from HeLa cells, SV40-transformed human fibroblasts, human placenta and human teratocarcinoma cell lines. These clones have enabled us to sequence the entire coding region of Gd. Thus, the entire amino acid sequence of human G6PD is provided for the first time. This work is the first step for structural analysis of G6PD variants and for an understanding of the biological features of this enzyme at the molecular level.